2014
DOI: 10.3329/sja.v11i1.18386
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of sunflower (Helianthus annus L.) as influenced by nitrogen, sulphur and farmyard manure under temperate conditions

Abstract: A field experiment was conducted at the Research farm, Division of Agronomy, Sher-e-Kashmir University of Agricultural Sciences and Technology, India for two consecutive rainy (kharif) seasons of 2009 and 2010 to find out the impact of nitrogen, sulphur and farmyard manure (FYM) on growth and yield of sunflower (Helianthus annuus L.). Application of 120 kg N ha -1 significantly increased all the yield components viz., plant height, leaf area index, dry matter production, capitulum diameter, achenes capitulum -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 3 publications
3
24
0
3
Order By: Relevance
“…Rasool, Hassan, and Jahangir (2013) observed that as N doses increased, grains production and oil yield also increased; additionally, grains oil content decreased when high N doses were applied.…”
Section: Grain and Oil Productionmentioning
confidence: 89%
See 1 more Smart Citation
“…Rasool, Hassan, and Jahangir (2013) observed that as N doses increased, grains production and oil yield also increased; additionally, grains oil content decreased when high N doses were applied.…”
Section: Grain and Oil Productionmentioning
confidence: 89%
“…The search for genotypes that efficiently use N by optimizing N fertilization has been the subject of several studies on important agronomical crops (Avice & Etienne, 2014). N is essential for sunflower grain production and oil extraction (Rasool, Hassan, & Jahangir, 2013). Abdel-Motagally and Osman (2010) observed how increased soil N through fertilization influenced several growth parameters (plant height, stem diameter, head diameter, 100-seed weight, seed yield plant ), causing production increases.…”
Section: Introductionmentioning
confidence: 99%
“…High percentage poly-unsaturated fatty acids in sunflower oil such as linoleic acid in classical sunflower, which can reach up to 90% of the total unsaturated fatty acids, makes it high-quality edible oil commercially (1) . Its seed has a good percentage of crude fibre (16-27), ash (2)(3), soluble sugar (7)(8)(9) and hull (21-27) (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Its rank as a source of edible oil in the world is the fourth next to soybean, palm oil and canola (Osman and Awed, 2010). It contains a good percentage (48-53) of oil (Rasool et al, 2013). It has a great potential in bridging the gap between demand and supply of edible oil to a significant extent in the years to come (Abd El-Mohsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated use of biofertilizer sourc es of nutrients is very important for higher productivity and sustainability (Rasool et al, 2013). Keeping these aspects in view, the present investigation aimed to assess the impact of applying different concentrations of seaweed liquid extract (SWLE) by soaking seeds and / or coating it with A. lipoferaum suspension on growth and productivity of sunflower (Helianthus annuus L.) in newly reclaimed soils.…”
Section: Introductionmentioning
confidence: 99%